Некоторые вопросы топонимики центральных районов страны Хатти - Хачатрян, В. H. (1976)
Chačatrjan/Khachatrian, Valeri; Some problems relating to the toponymy of the Central Regions of the land of Hatti; engl. Résumé S. 288; Gebiet von Hattuša, Kartapaḫa, Šalma, Paršananḫila, Šamlušna.